Low-cost Ti-V-Zr metastable beta titanium alloy for laser additive and preparation method of low-cost Ti-V-Zr metastable beta titanium alloy

By adopting low-cost Ti-V-Zr metastable β titanium alloy and laser additive process, combining plasma heating and high-speed rotation and other steps to prepare metal powder, and undergo solid solution and water quenching treatment, the existing metastable β titanium alloy production cost and process problems are solved, and high-strength, high plasticity and low-cost laser additive Ti-V-Zr metastable β titanium alloy is realized.

CN119640091APending Publication Date: 2025-03-18KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411822279.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing metastable β-titanium alloy has high production costs and long production cycles. The laser additive process has problems such as pores, inclusions, and uneven composition, which affects the mechanical properties and application of the materials.

Method used

The low-cost Ti-V-Zr metastable β titanium alloy is used to prepare metal powders through plasma heating and high-speed rotation, and one-way deposition is performed using laser additive technology, combined with solid solution and water quenching treatment to obtain excellent laser additive Ti-V-Zr metastable β titanium alloy.

Benefits of technology

It has achieved low-cost metastable β-titanium alloy preparation, good material forming properties, uniform structure, and highly matched strength and plasticity, avoiding defects in the additive manufacturing process and shortening the preparation cycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640091A_ABST
    Figure CN119640091A_ABST
Patent Text Reader

Abstract

The invention relates to a low-cost Ti-V-Zr metastable beta titanium alloy for laser additive manufacturing and a preparation method of the low-cost Ti-V-Zr metastable beta titanium alloy, and belongs to the technical field of metastable beta titanium alloy additive manufacturing. The alloy comprises the following components in percentage by weight: 18-25% of V, 1-5% of Zr and the balance of Ti and inevitable impurities, wherein the sum of the components is 100%. A corresponding metal cylindrical bar is prepared according to the mass ratio of Ti, V and Zr elements; and under the argon atmosphere, all the metal cylindrical bars are placed at the plasma heating end, high-speed rotation is conducted, the cylindrical end faces are melted into liquid, the liquid is crushed and refined under the centrifugal force effect, cooling, solidification and spheroidizing are conducted in a lower powder collecting chamber, and the metastable beta titanium alloy powder for the laser additive is obtained. Metastable beta titanium alloy powder for laser additive manufacturing is placed in a powder feeder to be subjected to one-way deposition, and a component is formed through set laser parameters; and carrying out solid solution and water quenching on the component to obtain the laser additive Ti-V-Zr metastable beta titanium alloy. The Ti-V-Zr metastable beta titanium alloy prepared through the method is highly matched in strength and plasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-cost Ti-V-Zr metastable beta titanium alloy for laser additive manufacturing and a preparation method thereof, belonging to the technical field of metastable beta titanium alloy additive manufacturing. Background Art

[0002] Metastable β titanium alloys are favored by the aerospace industry due to their superior mechanical properties. They are often used in aircraft structural materials and are of great significance to the development of high-end aerospace manufacturing. However, the high cost of raw materials and long production cycle of such alloys limit their further development and application. In order to improve their economic practicality, it is necessary to develop low-cost metastable β titanium alloy models and explore suitable preparation processes to shorten the production cycle.

[0003] Metastable β titanium alloys need to add a certain amount of isomorphous β stabilizing elements. The metastable titanium alloys that have been studied so far contain a large amount of high-priced β stabilizing elements such as Mo, Nb, Ta, etc. For example, the patent application number is 2023112424598, and the name is "A method for preparing a fast strain hardening double yield metastable titanium alloy". The composition of the metastable β titanium alloy disclosed in the patent application is Nb: 17.wt%, Fe: 2.wt%, Al: 2.wt%, and the balance is commercial pure Ti and unavoidable impurities. The addition of a large amount of Nb increases the production cost. Therefore, using relatively cheap isomorphous V as the main additive element is an important idea for designing low-cost metastable β titanium alloys. The β stability and solid solution strengthening ability of V element are stronger than Nb and Ta, and slightly weaker than Mo. In theory, adding a small amount or a considerable amount can stabilize the β matrix, thereby greatly reducing costs.

[0004] The traditional preparation process of metastable β titanium alloy is relatively cumbersome. Since metastable titanium alloy contains a large amount of β-stabilizing elements, component segregation - the "β spot" phenomenon - often occurs in traditional casting and forging processes, which is not conducive to the plasticity of the alloy and is often combined with more post-processing methods. For example, the patent application number is CN202410088440.0, entitled "A high-plasticity, high-strain hardening metastable β titanium alloy and its preparation method", which involves methods including repeated vacuum arc melting, vacuum homogenization annealing, multi-pass hot rolling deformation and solution air cooling. In contrast, the increasingly popular laser additive process in recent years has shown great advantages. The unique metallurgical conditions such as instantaneous small molten pool and ultra-high temperature can homogenize the material composition, and the non-equilibrium solidification conditions such as extraordinary high temperature gradient and rapid cooling rate can retain a large amount of metastable β phase, which provides a revolutionary way to simplify the production and manufacturing process of metastable β titanium alloy.

[0005] At present, there are few reports on the research of laser additive manufacturing of metastable β titanium alloys. The existing literature still has the following process problems: 1. The non-equilibrium solidification state of laser-formed metals inevitably introduces pores and inclusions, causing premature fracture of the material. 2. Complex temperature and thermal stress cycles result in uneven material organization and composition. 3. The large temperature gradient in the deposition direction is easy to form columnar β grains with strong anisotropy, and there is room for further adjustment of laser processability. In addition, some studies have attempted to weaken the adverse effects of factors such as pores and inclusions introduced into the additive manufacturing process by regulating the twin effect. The deformation twin mechanism seems to be insensitive to this and can still coordinate the stress-strain process of the organization. The material strength and plasticity are highly adapted. It can be seen that metastable β titanium alloy is a material with the potential to develop into a high-performance titanium alloy for additive manufacturing. If its production cost can be further reduced and the laser process parameters can be optimized, it will be of great significance to the development and application of this type of alloy. Summary of the invention

[0006] In view of the problems and shortcomings of the above-mentioned prior art, the present invention provides a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing and a preparation method thereof. The Ti-V-Zr metastable β titanium alloy prepared by the present invention has good formability and uniform structure, and no macroscopic pores are observed in the deposited sample. In addition, the strength and plasticity are highly matched.

[0007] The present invention is achieved through the following technical solutions.

[0008] A low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing comprises, by mass percentage, 18% to 25% V, 1% to 5% Zr, the remainder being Ti and unavoidable impurities, the above components totaling 100%.

[0009] The low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing comprises, by mass percentage, 19% V, 1.5% Zr, and the remainder Ti and unavoidable impurities, the above components totaling 100%.

[0010] The low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing comprises, by mass percentage, 22% V, 4% Zr, the remainder being Ti and unavoidable impurities, the above components totaling 100%.

[0011] A method for preparing a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing, the specific steps of which include:

[0012] Step 1: According to the mass proportion of Ti, V and Zr elements, the corresponding metal cylindrical bar is prepared;

[0013] Step 2: Under an argon atmosphere, all the metal cylindrical rods obtained in step 1 are placed at the plasma heating end, and rotated at high speed to melt the cylindrical end surface into liquid, and crushed and refined under the action of centrifugal force, and cooled in the powder collection chamber below for 8 to 15 minutes, solidified and spheroidized to form metal powder, and sieved and mechanically mixed to obtain metastable β titanium alloy powder for laser additive with a particle size of 100-150 μm;

[0014] Step 3, placing the metastable β titanium alloy powder for laser additive obtained in step 2 in a powder feeder, and performing unidirectional deposition by coaxial powder feeding, and forming a component of a target shape and size on a substrate by setting laser parameters;

[0015] Step 4: The component obtained in step 3 is subjected to solid solution treatment and water quenching treatment to obtain a laser-added Ti-V-Zr metastable β titanium alloy with excellent performance.

[0016] In step 1, the diameter of the metal cylindrical rods is 30 to 45 mm.

[0017] The high speed rotation in step 2 is 20000 rpm.

[0018] The laser parameters in step 3 are: laser power 1700 W, scanning rate 600 mm / min, powder feed rate 10 g / min, spot diameter 2.8 mm, overlap rate 50%.

[0019] In the step 4, the temperature of the solid solution is 900° C. to 950° C., and the holding time is 0.5 to 1 h.

[0020] The plastic deformation mode of the above-mentioned metastable titanium alloy is a mixed mechanism of mechanical twinning and dislocation slip.

[0021] The elements involved in the additive manufacturing of metastable titanium alloys of the present invention play the following roles:

[0022] Vanadium (V): The role of vanadium is mainly reflected in the following aspects: 1. It reduces the transformation temperature of the β phase, stabilizes the β phase, inhibits the martensitic transformation, and can retain the β phase to room temperature under the laser rapid cooling system, providing the basic conditions for strain-induced twinning, giving the material excellent laser additive manufacturing process performance, and avoiding cracking problems caused by stress accumulation. 2. Vanadium is a βTi isomorphous element with a BCC crystal structure. It can be dissolved in β-Ti in a large amount by substitution to form an infinite solid solution. Since the difference between the atomic radius of vanadium and titanium is small, the lattice distortion effect is small, and good plasticity can be achieved while ensuring strength. 3. The addition of vanadium can increase the supercooling zone of the solid-liquid solidification front component, thereby promoting non-uniform nucleation in the local area of ​​the solid-liquid interface, which is conducive to equiaxed crystal transformation and eliminates anisotropy. In addition, the lattice distortion caused by the solid solution of vanadium can also prevent grain growth. The interaction between the two together plays a role in refining the grains.

[0023] Zirconium (Zr): In addition to its similar solid solution strengthening and grain refinement effects as vanadium, zirconium also has the following effects: 1. Zirconium has a certain effect on phase stability, can reduce the martensitic transformation temperature and delay the formation of the ω phase, and inhibit harmful phases. 2. Zirconium and titanium have the same chemical structure and properties. Using Zr instead of Ti can improve the component tolerance of fine-tuning the twinning effect of metastable β titanium alloys, and plays an important role in the process of shape control. 3. It reduces the solidification temperature range, avoids obvious segregation, and effectively improves the additive manufacturing process performance of the alloy.

[0024] The beneficial effects of the present invention are as follows: 1) The metastable titanium alloy of the present invention uses a large amount of vanadium to replace other expensive β elements, and the cost is relatively low. 2) The Ti-V-Zr metastable titanium alloy has low density and high specific strength, which meets the design requirements of lightweight aerospace. The specific strength of the metastable titanium alloy provided by the present invention reaches 158.58 (N / ㎡) / (kg / m 3 ), good plasticity, tensile elongation of 27.5%; compared with other Ti-Mo-based, Ti-Ta-based, and Ti-Nb-based metastable titanium alloys, the plasticity is similar and has a higher specific strength. 3) By designing the alloy composition and controlling the powder ratio, the strain twinning effect in the alloy deformation is activated, and the alloy strength and plasticity are synergistically improved. At the same time, the material's damage tolerance is also improved, avoiding the poor serviceability of additive components due to additive manufacturing process defects. The additively manufactured metastable titanium alloy has strong plasticity adaptation and can be used in aviation structural parts to achieve aircraft weight reduction. 4) During the additive manufacturing process, there are no defects such as macroscopic pores, inclusions, segregation, etc. The additive manufacturing process has good performance and does not require post-processing methods such as forging and homogenization annealing. Good performance can be obtained by combining simple heat treatment, shortening the preparation cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Actual photo of the macroscopic morphology of the laser additively manufactured Ti-V-Zr alloy sample prepared in Example 1.

[0026] Figure 2 The dimensions of the laser additively manufactured Ti-V-Zr alloy plate strip-shaped tensile parts obtained in Example 1.

[0027] Figure 3 Metallographic micrograph of the laser additively manufactured Ti-V-Zr alloy sample obtained in Example 1.

[0028] Figure 4 Tensile strain twins of the Ti-V-Zr alloy laser additively manufactured sample prepared in Example 1.

[0029] Figure 5Tensile engineering stress-strain curve of the laser additively manufactured Ti-V-Zr alloy sample prepared in Example 1.

[0030] Figure 6 EDS photograph of the additive sample Ti-V-Zr alloy obtained in Example 1.

[0031] Figure 7 XRD spectrum of the additive sample Ti-V-Zr alloy obtained in Example 1.

[0032] Figure 8 This is a comparison chart of the specific strength-plasticity of the Ti-22V-4Zr alloy obtained in Example 1 and other metastable β titanium alloys. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods.

[0034] Example 1

[0035] The low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing comprises, by mass percentage, 22% V, 4% Zr, the remainder being Ti and unavoidable impurities, the above components totaling 100%.

[0036] The method for preparing a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing comprises the following specific steps:

[0037] Step 1, according to the total mass of 0.5kg, weigh 0.37kg of Ti, 0.11kg of V, and 0.02kg of Zr respectively to prepare corresponding metal cylindrical bars with a diameter of 30mm;

[0038] Step 2, under an argon atmosphere (argon flow rate of 0.05 m / s), place all the metal cylindrical rods obtained in step 1 at the plasma heating end (heating temperature of 3000°C), and rotate at high speed (high-speed rotation of 20000 rpm) to melt the cylindrical end surface into liquid, crush and refine under the action of centrifugal force, and cool in the powder collection chamber below for 8 minutes, solidify and spheroidize to form metal powder, sieve, and mechanically mix to obtain metastable β titanium alloy powder for laser additive with a particle size of 100-150 μm;

[0039] Step 3, the metastable β titanium alloy powder for laser additive obtained in step 2 is placed in a powder feeder, and unidirectional deposition is performed by coaxial powder feeding. By setting the laser parameters, the laser process parameters are set to: laser power 1700W, scanning rate 600mm / min, powder feeding rate 10g / min, spot diameter 2.8mm, overlap rate 50%, and finally, a block sample with a size of 60mm×75mm×15mm is deposited on the TC4 plate;

[0040] Step 4: The block sample obtained in step 3 is solid-solution treated at a temperature of 900°C for a holding time of 0.5 h, and then taken out and water quenched to obtain a laser-added Ti-V-Zr metastable β titanium alloy with excellent performance.

[0041] The room temperature tensile property test and microstructure characterization were performed on the low-cost Ti-V-Zr metastable β titanium alloy block sample for additive manufacturing prepared in this example.

[0042] Room temperature tensile properties test: Three pieces with the following sizes were cut from the additively manufactured block sample using wire EDM. Figure 2 The dog-bone plate tensile test was carried out on a UTM5000 electronic universal testing machine at room temperature. The tensile rate was set to 0.5 mm / min. The stress-strain curve is as follows: Figure 5 As shown in the figure, the alloy has a yield strength of 660Mpa and a tensile strength of 780Mpa, and a fracture elongation of 27.5%, with a high degree of strength and plasticity matching. In addition, the material still maintains an elongation of about 10% when entering the necking stage, and has good resistance to crack growth.

[0043] Characterization of microstructure: Cut a metal block of 5×5×5mm from the laser-added Ti-V-Zr metastable titanium alloy block sample as a metallographic sample to observe the microstructure. In addition, a portion of the broken plate sample was cut to characterize the tensile structure. The experiment first used 60, 180, 400, 1000, and 2000 mesh SiC sandpaper for rough polishing, and then used 1μm diamond suspension for rough polishing and 0.05μm diamond suspension + 10% H2O2 hydrogen peroxide for fine polishing. Finally, HF (hydrofluoric acid): HNO3 (nitric acid): H2O (water) = 1:2:17 (volume fraction, vol.%) to corrode the metallographic sample, and the corrosion time was 5s to 12s. The corroded sample was placed under an optical microscope to observe the morphology. Figure 3 The microstructure of the laser additive sample is shown. The grains are equiaxed, and there are no defects such as pores and unmelted particles. Figure 4 This shows strain twinning after stretching. Figure 6 It proves that the material composition is uniform and there is no segregation; Figure 7 XRD shows that the alloy is a BCC single-phase structure, and the intensity ratio of the diffraction peak is consistent with the characteristics of polycrystalline BCC materials, with no preferred orientation.

[0044] The specific strength-plasticity comparison of the Ti-22V-4Zr alloy prepared in this example and other metastable β titanium alloys is shown in the figure below: Figure 8 As shown, from Figure 8It can be seen that the specific strength of the metastable titanium alloy (Ti-22V-4Zr alloy) provided by the present invention reaches 158.58 (N / ㎡) / (kg / m 3 ), good plasticity, tensile elongation of 27.5%. Compared with metastable β titanium alloys such as Ti-25Nb-3Zr-3Mo-2Sn, Ti-25Nb-0.7Ta-2Zr, Ti-12Mo-10Zr, and Ti-15Mo-0.3O, the plasticity is slightly lower, but the laser-added Ti-22V-3Zr metastable β titanium alloy has a high specific strength; compared with high-strength materials such as Ti-12Mo-6Zr-2Fe, Ti-15Mo-5Zr-3Al, and Ti-15Mo, the specific strength is slightly lower, but it has better plasticity. The alloy prepared in this embodiment has good specific strength and plasticity, and balanced mechanical properties.

[0045] Example 2

[0046] The low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing comprises, by mass percentage, 19% V, 1.5% Zr, and the remainder Ti and unavoidable impurities, the above components totaling 100%.

[0047] The method for preparing a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing comprises the following specific steps:

[0048] Step 1, according to the total mass of 0.5kg, weigh 0.3975kg of Ti, 0.095kg of V, and 0.0075kg of Zr respectively to prepare corresponding metal cylindrical bars with a diameter of 45mm;

[0049] Step 2: Under an argon atmosphere (argon flow rate of 0.05 m / s), place all the metal cylindrical rods obtained in step 1 at the plasma heating end (heating temperature of 3000°C), and rotate at high speed (high-speed rotation of 20000 rpm) to melt the cylindrical end surface into liquid, crush and refine under the action of centrifugal force, and cool in the powder collection chamber below for 15 minutes, solidify and spheroidize to form metal powder, sieve, and mechanically mix to obtain metastable β titanium alloy powder for laser additive with a particle size of 100-150 μm;

[0050] Step 3, the metastable β titanium alloy powder for laser additive obtained in step 2 is placed in a powder feeder, and unidirectional deposition is performed by coaxial powder feeding. By setting the laser parameters, the laser process parameters are set to: laser power 1700W, scanning rate 600mm / min, powder feeding rate 10g / min, spot diameter 2.8mm, overlap rate 50%, and finally, a block sample with a size of 60mm×75mm×15mm is deposited on the TC4 plate;

[0051] Step 4: The block sample obtained in step 3 is solid-solution treated at a temperature of 950°C for 1 hour, and then taken out and water quenched to obtain a laser-added Ti-V-Zr metastable β titanium alloy with excellent performance.

[0052] The properties of Ti-18V-Zr prepared in this example are shown in Table 1.

[0053] Table 1

[0054]

[0055] Example 3

[0056] The low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing comprises, by mass percentage, 25% V, 5% Zr, the remainder being Ti and unavoidable impurities, the above components totaling 100%.

[0057] The method for preparing a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing comprises the following specific steps:

[0058] Step 1, according to the total mass of 0.5kg, weigh 0.350kg of Ti, 0.125kg of V, and 0.025kg of Zr respectively to prepare corresponding metal cylindrical bars with a diameter of 45mm;

[0059] Step 2, under an argon atmosphere (argon flow rate of 0.05 m / s), place all the metal cylindrical rods obtained in step 1 at the plasma heating end (heating temperature of 3000°C), and rotate at high speed (high-speed rotation of 20000 rpm) to melt the cylindrical end surface into liquid, crush and refine under the action of centrifugal force, and cool in the powder collection chamber below for 10 minutes, solidify and spheroidize to form metal powder, sieve, and mechanically mix to obtain metastable β titanium alloy powder for laser additive with a particle size of 100-150 μm;

[0060] Step 3, the metastable β titanium alloy powder for laser additive obtained in step 2 is placed in a powder feeder, and unidirectional deposition is performed by coaxial powder feeding. By setting the laser parameters, the laser process parameters are set to: laser power 1700W, scanning rate 600mm / min, powder feeding rate 10g / min, spot diameter 2.8mm, overlap rate 50%, and finally, a block sample with a size of 60mm×75mm×15mm is deposited on the TC4 plate;

[0061] Step 4: Solvent-treat the block sample obtained in step 3 at a temperature of 920°C for 0.8 h, then take it out and water quench it to obtain a laser-added Ti-V-Zr metastable β titanium alloy with excellent performance.

[0062] The properties of Ti-25V-5Zr prepared in this example are shown in Table 2.

[0063] Table 2

[0064]

[0065] The specific implementation modes of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing, characterized in that: The composition includes 18% to 25% V, 1% to 5% Zr, and the remainder is Ti and inevitable impurities, and the above components total 100%.

2. The low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing according to claim 1, characterized in that: The composition, by mass percentage, includes 19% V, 1.5% Zr, and the remainder is Ti and inevitable impurities, and the above components total 100%.

3. The low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing according to claim 1, characterized in that: The composition, by mass percentage, includes 22% V, 4% Zr, and the remainder is Ti and inevitable impurities, and the above components total 100%.

4. A method for preparing a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing according to any one of claims 1 to 3, characterized in that The specific steps include: Step 1: According to the mass proportion of Ti, V and Zr elements, the corresponding metal cylindrical bar is prepared; Step 2: Under an argon atmosphere, all the metal cylindrical rods obtained in step 1 are placed at the plasma heating end, and rotated at high speed to melt the cylindrical end surface into liquid, and crushed and refined under the action of centrifugal force, and cooled in the powder collection chamber below for 8 to 15 minutes, solidified and spheroidized to form metal powder, and sieved and mechanically mixed to obtain metastable β titanium alloy powder for laser additive with a particle size of 100-150 μm; Step 3, placing the metastable β titanium alloy powder for laser additive obtained in step 2 in a powder feeder, and performing unidirectional deposition by coaxial powder feeding, and forming a component of a target shape and size on a substrate by setting laser parameters; Step 4: The component obtained in step 3 is subjected to solid solution treatment and water quenching treatment to obtain a laser-added Ti-V-Zr metastable β titanium alloy with excellent performance.

5. The method for preparing a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing according to claim 4, characterized in that: In step 1, the diameter of the metal cylindrical rods is 30 to 45 mm.

6. The method for preparing a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing according to claim 4, characterized in that: The high speed rotation in step 2 is 20000 rpm.

7. The method for preparing a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing according to claim 4, characterized in that: The laser parameters in step 3 are: laser power 1700 W, scanning rate 600 mm / min, powder feed rate 10 g / min, spot diameter 2.8 mm, overlap rate 50%.

8. The method for preparing a low-cost Ti-V-Zr metastable β titanium alloy for laser additive manufacturing according to claim 4, characterized in that: In step 4, the temperature of the solid solution is 900° C. to 950° C., and the holding time is 0.5 to 1 h.

Citation Information

Patent Citations

  • High-plasticity high-strain-hardening metastable beta titanium alloy and preparation method thereof

    CN117926075A